Opportunities and Strategies For Women's Economic Empowerment Through Online Media - Nita Ainun Nadjah; Abdul Mukhlis; Nurhannah Widiyanti; Sacandra Aji Rivaldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
The global Covid-19 pandemic has affected almost all lines of human life without exception, be it economic, educational, social, or other aspects. One of the sectors which, according to the author, is the most affected is the economy. The implementation of social restrictions during Covid-19 has reduced the income of some people and lose their jobs. Men and women alike are the objects that are harmed. However, there is an interesting phenomenon that deserves attention, namely, the proliferation of digital businesses carried out by women. The author tries to capture this phenomenon using a qualitative descriptive method. Furthermore, the empowerment carried out by the author and the team utilizes the SL (Service Learning) method. In addition, the author also tries to offer a conceptual formula in the form of a women's empowerment strategy based on simple observations in the field. The result of this study of women's economic empowerment is the increase in women's creativity in making products that sell value through online marketing. It is hoped that this empowerment activity will be able to elevate the dignity and independence of the community, especially women.